Agribio-technological governance and environmental justice. Tensions around the release of GMO’s in Brasil, Mexico and Argentina - Berger, Mauricio; Carrizo, Cecilia (Política. Revista de Ciencia Política, 2016)
Our framework is a research on ways in which democratic political practices are updated in contexts of capitalism by dispossession. In this article, we investigate institutional wefts and struggles for rights-at national and transnational scalesaround the definition of experimental and commercial approval of genetically modified seeds. We make use of the notions of networks and governance to give account for the complex interactions of state-public actors, citizens and private actors, who oppose their powers to produce a normative order and enforce it. We try to reconstruct theoretically and empirically those interconnections, interferences and tensions in these networks, through case studies of Argentina, Brazil and Mexico.